Inspiratory muscle fatigue after race-paced swimming is not restricted to the front crawl stroke - Lomax, M.; Iggleden, C.; Tourell, A.; Castle, S.; Honey, J. (The Journal of Strength and Conditioning Research, 2012)
The occurrence of inspiratory muscle fatigue (IMF) has been documented after front crawl (FC) swimming of various distances. Whether IMF occurs after other competitive swimming strokes is not known. The aim of the present study was to assess the impact of all 4 competitive swimming strokes on the occurrence of IMF after race-paced swimming and to determine whether the magnitude of IMF was related to the breathing pattern adopted and hence breathing frequency (fb). Eleven, nationally ranked, youth swimmers completed four 200-m swims (one in each competitive stroke) on separate occasions. The order of the swims, which consisted of FC, backstroke (BK), breaststroke (BR), and butterfly (FLY), was randomized. Maximal inspiratory mouth pressure (MIP) was assessed before (after a swimming and inspiratory muscle warm-up) and after each swim with fb calculated post swim from recorded data. Inspiratory muscle fatigue was evident after each 200-m swim (p < 0.05) but did not differ between the 4 strokes (range 18-21%). No relationship (p > 0.05) was observed between fb and the change in MIP (FC: r = -0.456; BK: r = 0.218; BR: r = 0.218; and FLY: r = 0.312). These results demonstrate that IMF occurs in response to 200-m race-paced swimming in all strokes and that the magnitude of IMF is similar between strokes when breathing is ad libitum occurring no less than 1 breath (inhalation) every third stroke.